2008
DOI: 10.1038/ejcn.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Indices of fatness and relationships with age, ethnicity and lipids in New Zealand European, Māori and Pacific children

Abstract: Background/Objectives: To investigate the relationships between body mass index (BMI), body fatness, ethnicity, age and blood lipids. Subjects/Method: In a subsample (N ¼ 643) of the 2002 New Zealand Child Nutrition Survey (N ¼ 3275, age 5-14 years) consisting Māori (89 boys, 69 girls), Pacific (154 boys, 194 girls) and European (71 boys, 66 girls) ethnic groups, fat-free mass (FFM) was determined by bioimpedance analysis. FFM index (FFMI, FFM/height 2 ), fat mass index (FMI, fat mass/height 2 ) and percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
4
23
0
2
Order By: Relevance
“…At age 6 children in the PIF cohort with highest birth weights were heaviest 5 while for the children with the smallest birth weights weight gain over their first 6 years was more rapid than other children in the cohort. Furthermore, an Auckland sample from the National Children's Nutrition Survey showed Pacific girls and boys, aged between 5 to 14 years, increased in fat free mass (FFM) and fat mass (FM) faster than their European or Māori counterparts 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At age 6 children in the PIF cohort with highest birth weights were heaviest 5 while for the children with the smallest birth weights weight gain over their first 6 years was more rapid than other children in the cohort. Furthermore, an Auckland sample from the National Children's Nutrition Survey showed Pacific girls and boys, aged between 5 to 14 years, increased in fat free mass (FFM) and fat mass (FM) faster than their European or Māori counterparts 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Heavier children are also more likely to have a higher prevalence of cardiometabolic risk factors 6,17 . These findings support the requirement for action points for detection of cardiometabolic abnormalities to be based on historical data which precedes or circumvents the current obesity epidemic.…”
mentioning
confidence: 99%
“…Overfeeding and the excessive growth of adipose tissue in young children burden their bodies and lead to a variety of health problems that can manifest themselves during adolescence or many years later (Geiẞ et al 2001, Brouwer et al 2013). Body fat is strongly associated with total cholesterol and high-density lipoprotein (HDL) cholesterol (Rush 2009). Importantly, excess body weight predicts not only medical problems in children but also social and educational ones (Janssen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported this in Asian, African and indigenous populations, often compared with Caucasians. [7][8][9][10][11][12][13] However, information is lacking on differences between, for example, various Caucasian populations within Europe.…”
Section: Introductionmentioning
confidence: 99%